English Fricatives Sound Pronounced by The Students’ - Ika Agustina; Andi Suwarni; Dewi Sartika; Rahmiati (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
In speaking, a good pronunciation is needed in order the communication will be run well. The purpose of this study was to know the sounds produced by fricatives in English and the factors that cause students to mispronounce them. The writers hope that students will understand more about the use of fricative pronunciation and that the results of this study can be used as a reference in teaching English, especially when pronouncing fricatives. This study focused on the description of fricatives. They were obtained from the eighth semester undergraduate students of the English Education department, University of Muhammadiyah Bone. The method of this study was a descriptive qualitative method. This data was obtained through interviews with students in the Department of English Education and analyzed the mispronunciation of English fricatives. As a result, Kenworthy identified factors that influence students' pronunciation: (1) native language, (2) age factor, (3) number of contacts, (4) vocal ability, (5) motivation and good pronunciation. As a result, the [v] sound is replaced with [f], the [ð] sound is replaced with the [d] and [t] sounds, and the [θ] sound is replaced with [ t ] and the replacement of the sounds [ z ] with [ s ]. Consistent with phonetic deletion of fricatives, they eliminated fricatives and eliminated word-ending sounds [θ].